Biochemical characterization of an extreme alkaline and surfactant-stable keratinase derived from a newly isolated actinomycete Streptomyces aureofaciens K13. Issue 31 (8th April 2015) - Gong, Jin-Song; Wang, Yue; Zhang, Dan-Dan; Zhang, Rong-Xian; Su, Chang; Li, Heng; Zhang, Xiao-Mei; Xu, Zheng-Hong; Shi, Jin-Song
<x xml:space="preserve">Abstract</x> Streptomyces aureofaciens K13 keratinase exhibited distinct properties and showed significant potential in the detergent industry.